Evaluating the impact of improved crop varieties in the Sahelian farming systems of Niger - Zakari, S.; Manda, J.; Ibro, G.; Moussa, B.; Abdoulaye, T. (Elsevier, 2023)
Most people in Niger still rely heavily on agriculture as a source of income. However, low productivity, climate change, soil infertility, pests, and diseases are challenges faced by this sector. As a result, the nation suffers from a severe problem of food insecurity. Many investigations indicate that adopting improved crop varieties(ICVs) increases agricultural productivity. Using information gathered from 1784 farmers, this study assesses the effects of adopting improved crop varieties (ICVs) on household welfare. To analyze the data, we employ endogenous switching regression (ESR) and inverse probability-weighted regression adjustment (IPWRA) techniques. The analysis shows that the ICVs adoption significantly improves household income and food access in Niger's Sahelian region. The ESR model's average treatment effects estimate shows that the ICVs adoption raised per capita income, food expenditure, and household dietary diversity score (HDDS) by 75 %, 1.81 %, and 36.49 %, respectively. The IPWRA model yields similar results.